2014
DOI: 10.1111/jch.12422
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Kinase as Predictor of Blood Pressure and Hypertension. Is It All About Body Mass Index? A Follow‐Up Study of 250 Patients

Abstract: 2The correlation between creatine kinase (CK) and blood pressure (BP) was examined prospectively in 120 patients with persistent high CK and 130 individuals with normal CK. Hypertension was defined as systolic BP (SBP) ≥140 mm Hg or diastolic BP (DBP) ≥90 mm Hg or current use of antihypertensive medication. Baseline CK was weakly correlated with SBP (r=0.11, P=.07) and DBP (r=0.16, P=.01) at follow-up. Persons with persistent high CK had higher SBP (140.8 mm Hg vs 138.2 mm Hg) and DBP (83.2 mm Hg vs 81.0 mm Hg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Sex differences in CK-MB mass were previously studied only in apparently healthy subjects [ 25 , 38 ] and others evaluated the enzyme activity in hypertensive patients [ 39 , 40 ], acute coronary syndrome, and myocardial infarction [ 41 , 42 , 43 ]. Strunz et al (2011) reported that females had significantly lower level of CK-MB mass than males among apparently healthy subjects [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in CK-MB mass were previously studied only in apparently healthy subjects [ 25 , 38 ] and others evaluated the enzyme activity in hypertensive patients [ 39 , 40 ], acute coronary syndrome, and myocardial infarction [ 41 , 42 , 43 ]. Strunz et al (2011) reported that females had significantly lower level of CK-MB mass than males among apparently healthy subjects [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Much attention has been given recently to the potential role of these energy-related compounds in cardiometabolic diseases. For example, the high creatine kinase (CK) phenotype has been found in hypertension- and obesity-prone patients [ 4 , 5 , 6 ], and high CK activity has been reported to lead to dysfunctional vascular contractility and insulin resistance [ 6 ]. In addition, the biosynthesis of creatine from GAA is considered critical for methyl group consumption in humans [ 7 ], with altered methylation and consequent homocysteine production suggested as additional factors for cardiovascular disease risk [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the sCK level is higher in healthy men compared to women [ 17 ] and in black individuals compared to Caucasians [ 18 ]. sCK has been associated with muscle mass in studies comparing athletes to the general population [ 19 ], as well as with body mass index (BMI) [ 20 ] and lean body mass [ 21 ].…”
Section: Introductionmentioning
confidence: 99%